Identification of a chemically reacting system using modulating function - Bacani, Florinda T. (Animo Repository, 1994)
The set of differential equations based on energy and mass balance was used to describe the dynamics of a nonisothermal continuously stirred tank reactor (CSTR) which was extended to a batch reactor. For both reactors, exothermic reaction between sodium thiosulfate and hydrogen peroxide was carried out as a test process model. The resulting equation was restructured to make it suitable for the use of the modulating function method.In the study, a technique using Modulating Function was presented for identification of parameters. This method consists of extracting unknown coefficients by using definite integrals involving only recorded data and none of their derivatives. The consequent set of equations were finally solved by the least square approach. The results were generally good, though there were some noticeable quantitative discrepancies. Therefore, it is necessary to investigate further, the application of modulating function as a tool in system identification.